PEMBATALAN PERKAWINAN KARENA PAKSAAN ORANGTUA DALAM PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF INDONESIA (Studi Kasus Putusan Nomor 50/Pdt.G/2025/PA.Btl) - rosikhun_17r; irsan (LPPM STAI Muhammadiyah Probolinggo, 2025)
Marriage under the Indonesian legal system is a civil institution that requires the free and voluntary consent of both prospective spouses as a fundamental requirement for its validity. However, social realities reveal that parental coercion remains prevalent, leading to violations of individual autonomy in choosing a life partner. This article analyzes the decision of the Bantul Religious Court, Case Number 50/Pdt.G/2025/PA.Btl, as a case study of marriage annulment due to family pressure. The study aims to examine the ruling from the perspective of Indonesian positive law and Islamic law. Using a qualitative approach through literature review and legal document analysis, the findings indicate that the marriage was annulled because it lacked genuine consent from the petitioner, thereby violating Article 6(1) of the Marriage Law and Article 71 letter f of the Compilation of Islamic Law. In Islamic jurisprudence, fasakh is a legitimate mechanism for annulling marriages conducted under coercion, as the absence of ridha renders the contract invalid. The court's decision reflects not only legal validity but also a strong commitment to safeguarding individual rights, particularly women’s autonomy. This study emphasizes the importance of legal education, institutional support, and social advocacy in preventing forced marriages